Determinan Kualitas Audit dimoderasi oleh Komite Audit - Helmi, Syarif M; Heniwati, Elok; Kurniadi, Ahmad; Faisal , Ahmad (Owner : Riset dan Jurnal Akuntansi, 2024)
This study aims to analyze the factors that influence audit quality variables, especially audit tenure and the reputation of the Public Accounting Firm. In addition, this study examines whether the audit committee can strengthen or weaken the improvement of audit quality in the company. This study uses quantitative methods, and the data source is secondary data. The population of this study consists of 30 IDX companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2021. The population and sample in this study are IDX 30 companies listed on the IDX in the 2016-2021 period. The sample was selected using the purposive sampling method. There are 16 companies listed on the Indonesia Stock Exchange in IDX, 30 companies during 2016-2021 that match the researcher's criteria. The analytical methods used in this study include descriptive statistical analysis, logistic regression analysis, and moderation hypothesis testing using moderated regression analysis. This study found that audit tenure has no impact on audit quality. However, KAP size was found to affect audit quality significantly. The Audit Committee is unable to moderate the effect of Audit Tenure on Audit Quality; The Audit Committee is unable to moderate the effect of KAP size on audit quality.